Analisis Penerapan Sistem K3 Pada Proyek Pembangunan Gedung Rawat Inap RSUD Hasri Ainun Habibie - Nur Indah M. Kau; Arfan Utiarahman; Apryanto A. Pahrun (Transbahasa, 2025)
The construction sector is among the industries with the highest rate of workplace accidents, making the implementation of an effective Occupational Safety and Health (OSH) system crucial. This study analyzes the application of OSH practices in the construction project of the Hasri Ainun Habibie Regional Public Hospital’s inpatient building in Gorontalo. Employing a quantitative descriptive approach, data were collected from 15 respondents, including safety experts, contractors, consultants, and workers, using questionnaires and interviews. The data were analyzed using the Relative Importance Index (RII) to assess the level of OSH implementation based on policy, training, use of personal protective equipment (PPE), emergency response procedures, and accident risk management. The findings indicate that the overall implementation of OSH in this project is categorized as “highly applied,” with the highest RII score of 0.93 for worker health insurance coverage and 0.95 for accident handling readiness, reflecting effective emergency preparedness. However, some areas, such as routine health checks and waste management, require further improvement. The study provides practical recommendations for strengthening OSH practices in healthcare facility construction projects, which involve higher safety risks and operational complexity than general construction projects. These findings are expected to serve as references for contractors, consultants, and policymakers in developing adaptive safety strategies aligned with regulatory standards.